Rekonstruksi Konsep Pembelajaran Mendalam (Deep Learning) dalam Pendidikan Islam (Analisis Isi terhadap Integrasi Nilai-Nilai Pemikiran KH. Ahmad Dahlan, KH. Hasyim Asy’ari, dan Ki Hajar Dewantara) - Alfi Noer Diana Hafidah; Ahmad Syaifullah; Yasril Gunawan; Beni Zakaria Fitriyanto; Ahsan Hakim (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
Education today tends to be oriented towards the transfer of knowledge and ignores the moral and spiritual dimensions. As a result, the learning process loses its humanistic meaning as a means of forming civilized human beings. This research aims to reconstruct the concept of deep learning in the perspective of Islamic Education through the analysis of the values of KH's thought. Ahmad Dahlan, KH. Hasyim Asy'ari, and Ki Hajar Dewantara. The method used is library research with a content analysis approach to the primary works of the three figures, namely Ahmad Dahlan's Book, Adab al-'Alim wa al-Muta'allim, and Part I: Education by Ki Hajar Dewantara, accompanied by secondary sources in the form of journals and education policy documents. The results of the study show that the three figures have a common point in the orientation of education: forming knowledgeable, moral, and civilized human beings. The core values of the three include the integration between knowledge and charity (Ahmad Dahlan), manners and sincerity in seeking knowledge (Hasyim Asy'ari), as well as freedom of learning and the balance of creation-rasa-karsa (Ki Hajar Dewantara). The synthesis of the three gave birth to the "Islamic Deep Learning" paradigm, which is a learning model that integrates cognitive, affective, and spiritual aspects in its entirety. Theoretically, this research expands the concept of deep learning with moral and spiritual dimensions; practically, it is the basis for the development of a humanistic, contextual, and transformative Islamic Education curriculum.